On the Reception of GDR Literature: Introduction - Patricia Herminghouse; Peter Uwe Hohendahl (GDR Bulletin, 1990)
Introduction to issue with articles from a November 1988 workshop in Washington, D.C. sponsored by the American Institute for Contemporary German Studies and the Goethe House New York.